Does excess weight interfere with bone mass accumulation during adolescence? - Nunes Mosca, Luciana [UNESP]; da Silva, Valéria Nóbrega [UNESP]; Goldberg, Tamara Beres Lederer [UNESP] (MDPI, 2013)
Obesity and osteoporosis are important global health problems characterized by increasing prevalence with high impact on morbidity and mortality. The objective of this review was to determine whether excess weight during adolescence interferes with bone mass accumulation. If bone mineral gain can be optimized during puberty, adults are less likely to suffer from the devastating complications of osteoporosis. The increased fracture risk in obese children has also been attributed to a lower bone mass for weight compared to non-obese children. Thus, adiposity present in this age group may not result in the protection of bone mass, in contrast to what has been observed in adults. However, studies involving adolescents have reported both protective and detrimental effects of obesity on bone. The results and mechanisms of these interactions are controversial and have not been fully elucidated, a fact highlighting the extreme relevance of this topic and the need to monitor intervening and interactive variables. © 2013 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Adolescents; Bone mineral density; Obesity; Osteoporosis; Overweight; Risk factors; 25 hydroxyvitamin D; adiponectin; ascorbic acid; colecalciferol; copper; ergocalciferol; glucose; leptin; magnesium; parathyroid hormone; phosphorus; protein; vitamin D; zinc; adipose tissue; anthropometry; body fat; bone density; bone mass; bone mineral; bone mineralization; calcium intake; diet supplementation; dual energy X ray absorptiometry; fat mass; glucose blood level; human; insulin resistance; insulinemia; lean body weight; obesity; osteopenia; osteoporosis; peripheral quantitative computed tomography; review; vitamin intake; weight reduction